PENGARUH KINERJA DALAM MENINGKATKAN KEPUASAN KERJA PERAWAT DI RUANG INTERNA RSUD MOH. ANWAR KABUPATEN SUMENEP - Zakiyah Yasin; Dian Ika Puspitasari (Fakultas Ilmu Kesehatan, 2014)
PerformanceJob satisfactionisanemotionalattitude offunandloves the job. The attitudeandmorale, disciplineandperformance.performanceis onethat affects thejob satisfactionof nurses. This study aimstodetermine the effect ofincreasing theperformance ofthejob satisfactionof nursesin thehospitalsInterneSumenep. The method usedis themethod ofanalyticresearchwithcross sectional approach. Total population of15nurses, the datacollectedbyquestionnairesandobservationswere analyzedusing theSpearmanRankTestStatisticsandRegressiontestwithsignificance level0.05. The results showed thatnurseswho have apoorperformancethenproducesbetter theperformanceis lessthanthe test resultsStatisticsshows theSpearmanRank(p =0.045<α =0.05) so thatH1is accepted, it meansthere isinfluence betweenperformanceand job satisfaction. Based on these resultsit can be concludedthat theperformance ofan effectin increasingthe job satisfactionof nurses. Keywords: NursePerformance, Job Satisfaction